Analysis of Effect of Temperature Variation Preheat on SMAW Welding of Microstructures, and ST60 and SS400 Steel Hardness - Habibi Palippui (Collaborate, 2023)
Welding is a metal joining process by melting some base and filler metals. SMAW welding (Shielded Metal Arc Welding) is one of the industry's most widely used welding methods. SMAW welding requires preheating (preheating) to reduce residual stress, distortion, and cold cracking in the weld metal. Preheat also can affect the microstructure and hardness of the weld metal. This study aims to analyze variations preheating on SS400 and ST60 steel against micro tests by SMAW welding, namely electric arc welding with covered electrodes. Temperature variation preheating used in SS400 steel was 140°C, 170°C, 300°C and 400°C in ST 60 steel. The results showed that the higher the temperature preheat, the larger the grain size of the microstructure in the parent metal region, the heat-affected area, and the weld metal area. The higher temperature preheat also led to a decrease in violence in the three areas. ST60 steel has a larger microstructure grain size and lower hardness than SS400 steel at all temperature variations preheat.